Purification of Pseudomonas aeruginosa exoenzyme S. - Woods, D E (Infect Immun, 1987)
Pseudomonas aeruginosa produces two distinct ADP-ribosyl transferases, exotoxin A and exoenzyme S, which differ in a number of properties including substrate specificity. Exoenzyme S was purified from culture supernatants of P. aeruginosa DG1. The procedure for purification consists of four major steps: ammonium sulfate precipitation, anion-exchange chromatography on DEAE-Sephacel, acetone precipitation in the presence of 1 M NaCl, and G-100 Superfine gel filtration chromatography. Exoenzyme S was monitored during purification by an assay for ADP-ribosyl transferase activity, mouse toxicity, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The purified material exhibited ADP-ribosyl transferase activity, reacted with monoclonal antibodies to exoenzyme S, and was toxic to mice and a variety of tissue culture cell lines. IMAGES: